CONFUSION OF EDUCATOR POLICY IN MINISTRY OF RELIGIOUS AFFAIRS 1945-2016 - Muh. Saerozi (State Islamic University North Sumatra, 2017)
Abstract: This essay examines the dynamics of the development of educator policy at the Ministry of Religious Affairs, which begins with the educator concept in Education Law at the Ministry of Religious Affairs from 1945 to 2016, and what the philosophical meaning of the development of the concept is. It also uncover where the confusion of the concept of educators throughout the history. This essay concludes with the conceptual solutions to educator problems enshrined in the Educational Law. The author finds there is a change of educators' concept on every amendment to Education law, each of which contains a specific philosophical meaning. The concept of educator that has been changed still entails the some problems up to the present time. The confusion of the concept in the law affects the regulation of educators in the Ministry of Religious Affairs, and thus it needs to be revised and finds alternative solution as offered in this paper. Abstrak: Kerancuan Kebijakan Pendidik di Kementerian Agama 1945-2016. Esai ini mengkaji dinamika perkembangan kebijakan pendidik pada Kementerian Agama, yang diawali dengan konsep pendidik dalam undang-undang pendidikan dan peraturan Menteri Agama sejak tahun 1945 sampai 2016, dan apa makna filosofis dari perkembangan konsep tersebut. Selanjutnya diungkap dimana letak kerancuan konsep pendidik dalam sepanjang sejarah tersebut. Pada bagian akhir difokuskan untuk menemukan solusi konseptual terhadap problem pendidik yang terdapat dalam undang-undang pendidikan. Penulis menemukan ada perubahan konsep pendidik pada setiap perubahan undang-undang pendidikan, yang memuat makna filosofis yang spesifik. Konsep pendidik yang telah diubah masih menyisakan masalah sampai sekarang. Kerancuan konsep dalam undang-undang berdampak pada peraturan pendidik di Kementerian Agama, sehingga perlu dilakukan revisi sebagaimana alternatif yang ditawarkan dalam tulisan ini. Keywords: education, Religious Affairs Ministry, policy, teacher, educational support personnel